Public Policy and Financial Regulation in Housing Sector (Case Study: One Million Houses and KPR FLPP) - Maria Dellarosawati Idawicaksakti; Monica Dianrosawati Itaratnasari; Raden Aswin Rahadi (School of Industrial and System Engineering, Telkom University, 2022)
During Jokowi’s tenure, a lot of programs and policies that focusing on housing sector were built byhim. Package of Economic Policy XIII is one of many policy’s package that Jokowi develop formanaged housing of people who have low income (MBR) with target that chosen is built onemillion houses. The lack of availability of housing for low-income people, is one of the reasons forthe policy package. In this research, author used qualitative method to analyst the phenomenon. Theresults of this study are the high rate of housing backlogs, the difficulty of obtaining housing ataffordable prices, and discussing KPR schemes in Indonesia. The existence of these governmentprograms does not significantly eliminate the phenomenon of housing a backlog. In addition, theexistence of the program must be accompanied by high supervision from the government andaccompanied by laws that bind violators.